The hazards of excessive screen time: Impacts on physical health, mental health, and overall well-being - Khumukcham A Devi; Sudhakar K Singh (Wolters Kluwer Medknow Publications, 2023)
Excessive screen time is a growing concern in modern society, with the proliferation of digital devices contributing to increased sedentary behavior and potential hazards to physical health, mental health, and overall well-being. This article explores the potential health and mood deterioration caused by excess screen time. In particular, the article examines how excessive screen time can affect physical health, mental health, and overall well-being. The physical hazards of excess screen time include eye strain, neck and shoulder pain, and back pain. Mental health hazards include increased levels of depression, anxiety, and other mood disorders. Overall well-being can also be impacted by excessive screen time, particularly when it comes to social relationships and cognitive development. The article concludes by recommending the limitation of screen time, particularly for young people, and the incorporation of physical activity and face-to-face interaction into daily routines.